Characteristics of Gut Microbiome and Its Metabolites, Short-Chain Fatty Acids, in Children With Idiopathic Short Stature - Li, Lin; Chen, Lifen; Yang, Yuanyan; Wang, Junqi; Guo, Li; An, Jingjing; Ma, Xiaoyu; Lu, Wenli; Xiao, Yuan; Wang, Xinqiong; Dong, Zhiya (Frontiers in Endocrinology, 2022)
Abstract Background: The gut microbiome is important for host nutrition and metabolism. Whether the gut microbiome under normal diet regulate human height remains to be addressed. Our study explored the possible relationship between gut microbiota, its metabolic products and the pathogenesis of idiopathic short stature disease (ISS) by comparing the gut microbiota between children with ISS and of normal height, and also the short-chain fatty acids (SCFAs) produced by the gut microbiota. Methods: The subjects of this study were 32 prepubescent children aged 4-8 years. The fecal microbial structure of the subjects was analyzed by 16S rRNA high-throughput sequencing technology. The concentrations of SCFAs in feces were determined by gas chromatography-mass spectrometry. Results: The richness of gut microbiota in ISS group was decreased, and the composition of gut microbiota was significantly different between ISS group and control group. The relative abundance of nine species including family Ruminococcaceae and genera Faecalibacterium and Eubacterium, in ISS group was significantly lower than that in control group (P<0.05). The relative abundance of 10 species, such as those belonging to genus Parabacteroides and genus Clostridium, in ISS group was significantly higher than that in control group (P<0.05). The concentration of total SCFAs and butyrate in ISS group was significantly lower than that in control group. The correlation analysis among different species, clinical indicators, and SCFAs showed that the relative abundance of family Ruminococcaceae and genera Faecalibacterium and Eubacterium was positively correlated with the standard deviation score of height. Furthermore, the concentrations of total SCFAs and butyrate were positively correlated with serum insulin-like growth factor 1 (IGF-1)-SDS. Disease prediction model constructed based on the bacteria who abundance differed between healthy children and ISS children exhibited high diagnostic value (AUC: 0.88). Conclusions: the composition of gut microbiota and the change in its metabolite levels may be related to ISS pathogenesis. Strains with increased or decreased specificity could be used as biomarkers to diagnose ISS.